A survey on sliding mode control for networked control systems. Issue 6 (26th April 2021) - Hu, Jun; Zhang, Hongxu; Liu, Hongjian; Yu, Xiaoyang
Abstract : In the framework of the networked control systems (NCSs), the components are connected with each other over a shared band-limited network. The merits of NCSs include easy extensibility, resource sharing, high reliability and so forth. However, the insertion of the communication network brings many challenges, such as network-induced phenomena and cyber-security, which should be handled properly. On the other hand, the sliding mode control (SMC) has become an effective scheme for the synthesis of NCSs due to its strong robustness and SMC has wide applications in NCSs. In this paper, some recent advances on SMC for NCSs are reviewed. In particular, some new SMC schemes for NCSs subject to time-delay, packet losses, quantisation and uncertainty/disturbance are summarised firstly. Subsequently, the problem of SMC for NCSs under scheduling protocols is discussed, where different communication protocols are introduced for the energy saving purpose during the synthesis of NCSs. Next, some recent results on SMC for NCSs with actuator/sensor fault and cyber-attack are recalled. Finally, the conclusion is provided and the potential research challenges on SMC for NCSs are pointed out.